Investigating prevalence of pathogenic genes (ETA and TSST-1) in Staphylococcus aureus isolated from different wards of the hospitals by PCR method - Ramazanzadeh, Rashid; Mohammadi Talvar, Hadi; Mirzaii, Mahdi; Hasheminasab, Seyed Sajjad; Narenji, Hanar (International Journal of Scientific World, 2015)
Staphylococcus aureus is the most common pathogenic organisms in the hospitals and communities' infections. It is responsible for more than 80 percent of infectious diseases. The purpose of the present paper is to determine the incidence of Staphylococcus pathogenic genes isolated from different wards of hospitals by PCR method. This study included 61 Staphylococcus aureusisolates collected from different wards hospital, between 2011 and 2012 in University of Kurdistan (Toohhid and Besat hospitals). All isolates were previously identified as Staphylococcus aureusby a standard microbiological procedure. It isolates were incubated at 37ÄŠ for 24h on blood agar; single colonies were tested with tube and slide coagulase, catalase tests and growth on Manito salt agar. Following genomic DNA extraction, the presence of ETA, TSST-1 genes was analyzed by PCR.61 strains of Staphylococcus aureushave been isolated from different wards of the hospital. Frequency of tst gene was 81% and eta gene was 47%. Moreover, frequency of strains with both eta and tst genes was 40%. Results of the present paper indicate that the prevalence of Staphylococcusaureus results on prevalence of eta and tst genes, and this is a matter of concern.